2016
DOI: 10.5194/acp-16-1987-2016
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of O<sub>4</sub> slant column density to derive aerosol layer height from a space-borne UV–visible hyperspectral sensor: sensitivity and case study

Abstract: Abstract. The sensitivities of oxygen-dimer (O 4 ) slant column densities (SCDs) to changes in aerosol layer height are investigated using the simulated radiances by a radiative transfer model, the linearized pseudo-spherical vector discrete ordinate radiative transfer (VLIDORT), and the differential optical absorption spectroscopy (DOAS) technique.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(33 citation statements)
references
References 87 publications
(107 reference statements)
3
16
0
Order By: Relevance
“…Overall all the estimated NN retrieval uncertainties are in line with the theoretical sensitivity analyses of Park et al (2016), who found that the O 2 −O 2 at 477 nm is significantly influenced by aerosol optical properties (including ω 0 ), τ , particle size and A. In particular, a ω 0 uncertainty of 10 % was demonstrated to lead to the aerosol effective height (AEH) retrieval error ranging from 270 to 1440 m, depending on the aerosol types.…”
Section: Aerosol Layer Pressure Retrievalssupporting
confidence: 66%
See 4 more Smart Citations
“…Overall all the estimated NN retrieval uncertainties are in line with the theoretical sensitivity analyses of Park et al (2016), who found that the O 2 −O 2 at 477 nm is significantly influenced by aerosol optical properties (including ω 0 ), τ , particle size and A. In particular, a ω 0 uncertainty of 10 % was demonstrated to lead to the aerosol effective height (AEH) retrieval error ranging from 270 to 1440 m, depending on the aerosol types.…”
Section: Aerosol Layer Pressure Retrievalssupporting
confidence: 66%
“…The low sensitivity to retrieve ALP when particles are located at a very high altitude is directly due to the O 2 −O 2 complex and its vertical distribution. This was demonstrated by Park et al (2016): O 2 −O 2 concentration exponentially decreases with increasing atmospheric altitude.…”
Section: Aerosol Layer Pressure Retrievalsmentioning
confidence: 88%
See 3 more Smart Citations